Mutations of Ki-ras and p53 genes in colorectal cancer and their prognostic significance. Issue 11 (November 1994) - Morrin, M; Kelly, M; Barrett, N; Delaney, P
Abstract : The series of genetic changes leading to malignancy in colorectal cancer is well reported. This includes mutational activation of the proto-oncogene Ki-ras and mutation/deletion of the p53 tumour suppressor gene. The frequency of these mutations was investigated in a panel of 52 colorectal cancer patients using a combination of immunocytochemistry and non-radioactive, digoxigenin-labelled in situ hybridisation. Sixty two per cent (32 of 52) of the study population were positive for p53 overexpression and 36% (19 of 52) positive for Ki-ras mutation. Twenty seven per cent (14 of 52) of the patients expressed both mutations. Mutation of either the p53 or the Ki-ras gene did not correlate with Dukes's stage, tumour differentiation or 5 year survival rate of the patients. Most of the rectal carcinoma specimens (11 of 15) showed p53 over-expression but the significance of this was not supported statistically. Thus detection of molecular changes is becoming more amenable to incorporation into routine histological carcinoma assessment because of the advent of non-radioactive labelling in in situ hybridisation and antibodies suitable for paraffin wax embedded specimens. The significance of these mutations in disease prognosis, however, remains questionable.